Time-dependent Migration of Elements from Plastic-packaging Material into Food - W. Kadi, Mohammad (Asian Journal of Chemistry, 2016)
Packaging is important for the food industry. Migration of elements from packaging material into food has attracted interest because of possible contamination of the food. In this paper, behavior of migration with time was studied. Ca, Mg, Zn and K were used as examples for migration into food stimulant. The study shows that polymer material, time of contact and type of migrating elements after the migration process.